Reproductive health education of conscripts in Turkish Armed Forces: first evaluation of training courses. - Gungor, Sadettin; Bakir, Bilal; Akyuz, Aygul; Gocgeldi, Ercan; Acikel, Cengiz Han; Kaya, Tulay; Hasde, Metin; Gul, Rukiye; Yildirimkaya, Gokhan (Military Medicine, 2007)
Background: In the frame of the Reproductive Health Program of Turkish Armed Forces, conscripts have been given 1-day participatory, interactive courses by the field military medical trainers in all military garrisons.Methods: Pre- and posttest knowledge levels of soldiers were tested by 25 true-false questions. Demographic characteristics and test scores were routinely transferred from the training rooms to the reproductive health database by authorized field trainers using the network of the army. Two hundred forty-eight thousand seven hundred ninety-six soldiers with perfect entrance of data have been selected for descriptive analyses.Results: Of all the soldiers, 39.2% were born in 1984. Primary school graduates have constituted the largest group with 34.4%. Only 7.4% of the soldiers were married. The mean precourse score was 65.7% +/- 15.4%, while the postcourse score was 83.5 +/- 12.73% (SD) (p < 0.001). Those who used to live in the east region of Turkey have obtained significantly lower scores on both pre- and posttests in comparison to scores of those who used to live in other regions (p < 0.001). Groups based on five educational levels have obtained significantly different scores, ascending gradually from uneducated to the higher educational level (p < 0.001). The ratio of increase in knowledge was highest in the groups with the lowest educational level and unmarried (p < 0.001).Conclusion: Training courses seem to succeed in increasing the knowledge of conscripts, particularly of those with a low socioeconomic and cultural status. However, it requires time to determine whether this increase in knowledge level with promote behavioral change positively and will improve young males' own and their partners' reproductive health status.